Structural characterization of an unprecedented lectin-like antitumoral anti-MUC1 antibody. Issue 96 (19th November 2020) - Macías-León, Javier; Bermejo, Iris A.; Asín, Alicia; García-García, Ana; Compañón, Ismael; Jiménez-Moreno, Ester; Coelho, Helena; Mangini, Vincenzo; Albuquerque, Inês S.; Marcelo, Filipa; Asensio, Juan L.; Bernardes, Gonçalo J. L.; et al.
Abstract : The molecular basis of an anti-MUC1 antibody that recognizes the entire GalNAc unit as a primary epitope is disclosed. Abstract : The molecular basis of antibody 5E5, which recognizes the entire GalNAc unit as a primary epitope is disclosed. The antibody's contacts with the peptide are mostly limited to two residues, allowing it to show some degree of promiscuity. These findings open the door to the chemical design of peptide-mimetics for developing efficient anti-cancer vaccines and diagnostic tools.